Potent enhancement of transdermal absorption and stability of human tyrosinase plasmid (pAH7/Tyr) by Tat peptide and an entrapment in elastic cationic niosomes - Manosroi J. (2014)
Enhancement of transdermal absorption through rat skin and stability of the human tyrosinase plasmid (P) using Tat (T) and an entrapment in elastic cationic niosomes (E) were described. E (Tween61:cholesterol:DDAB at 1:1:0.5 molar ratio) were prepared by the freeze-dried empty liposomes (FDELs) method using 25% ethanol. TP was prepared by a simple mixing method. TPE was prepared by loading T and P in E at the T:P:E ratio of 0.5:1:160 w/w/w. For gel formulations, P, TP, PE and TPE were incorporated into Carbopol 980 gel (30 g of plasmid per 1 g of gel). For the transdermal absorption studies, the highest cumulative amounts and fluxes of the plasmid in viable epidermis and dermis (VED) were observed from the TPE of 0.31 ± 0.04 g/cm and 1.86 ± 0.24 g/cm/h (TPE solution); and 4.29 ± 0.40 g/cm and 25.73 ± 2.40 g/cm/h (TPE gel), respectively. Only plasmid from the PE and TPE could be found in the receiving solution with the cumulative amounts and fluxes at 6 h of 0.07 ± 0.01 g/cm and 0.40 ± 0.08 g/cm/h (PE solution); 0.10 ± 0.01 g/cm and 0.60 ± 0.06 g/cm/h (TPE solution); 0.88 ± 0.03 g/cm and 5.30 ± 0.15 g/cm/h (PE gel); and 1.02 ± 0.05 g/cm and 6.13 ± 0.28 g/cm/h (TPE gel), respectively. In stability studies, the plasmid still remained at 4 ± 2 °C and 25 ± 2 °C of about 48.00-65.20% and 27.40-51.10% (solution); and 12.34-38.31% and 8.63-36.10% (gel), respectively, whereas at 45 ± 2 °C, almost all the plasmid was degraded. These studies indicated the high potential application of Tat and an entrapment in elastic cationic niosomes for the development of transdermal gene delivery system. © 2013 Informa Healthcare USA, Inc.